2012
DOI: 10.1126/science.1220941
|View full text |Cite
|
Sign up to set email alerts
|

Global Honey Bee Viral Landscape Altered by a Parasitic Mite

Abstract: Emerging diseases are among the greatest threats to honey bees. Unfortunately, where and when an emerging disease will appear are almost impossible to predict. The arrival of the parasitic Varroa mite into the Hawaiian honey bee population allowed us to investigate changes in the prevalence, load, and strain diversity of honey bee viruses. The mite increased the prevalence of a single viral species, deformed wing virus (DWV), from ~10 to 100% within honey bee populations, which was accompanied by a millionfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
719
9
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(774 citation statements)
references
References 35 publications
42
719
9
4
Order By: Relevance
“…These results are in contrast to other studies around the world where Varroa mites played a significant or central role in colony losses (Bailey and Ball, 1991;Brodschneider et al, 2010;Dainat et al, 2012b;Dietemann et al, 2012;Guzman-Novoa et al, 2010;Ritter, 1981;Rosenkranz et al, 2010;Schäfer et al, 2010;Shimanuki et al, 1994). Also, the close association between Varroa mites and viruses (especially DWV, ABPV) and the subsequent colony losses they usually cause (Berthoud et al, 2010;Dainat et al, 2012a;Martin et al, 2012) were not observed in this study. Even though some apiaries in this study were occasionally infested with multiple pathogens and parasites, no obvious signs of disease were observed; thereby suggesting that the savannah honeybee population studied is resistant to these assaults.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These results are in contrast to other studies around the world where Varroa mites played a significant or central role in colony losses (Bailey and Ball, 1991;Brodschneider et al, 2010;Dainat et al, 2012b;Dietemann et al, 2012;Guzman-Novoa et al, 2010;Ritter, 1981;Rosenkranz et al, 2010;Schäfer et al, 2010;Shimanuki et al, 1994). Also, the close association between Varroa mites and viruses (especially DWV, ABPV) and the subsequent colony losses they usually cause (Berthoud et al, 2010;Dainat et al, 2012a;Martin et al, 2012) were not observed in this study. Even though some apiaries in this study were occasionally infested with multiple pathogens and parasites, no obvious signs of disease were observed; thereby suggesting that the savannah honeybee population studied is resistant to these assaults.…”
Section: Discussioncontrasting
confidence: 67%
“…The absence of DWV from the honeybee and Varroa mite samples collected during this study was unexpected given its high prevalence in apiaries around the world (Allen and Ball, 1996;Baker and Schroeder, 2008;Berényi et al, 2006;Chen and Siede, 2007;Ellis and Munn, 2005;Martin et al, 1998;Tentcheva et al, 2004a) and the close association of DWV with Varroa mites (Bailey and Ball, 1991;Bowen-Walker et al, 1999;Dainat et al, 2012a;Gisder et al, 2009;Martin et al, 2012;Yang and CoxFoster, 2005;Yue and Genersch, 2005). Recently, DWV was also found to be absent from wild A. m. scutellata drones collected in a South African Nature Reserve and honeybee samples from Uganda (Kajobe et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…deformed wing virus) outbreaks in the honeybee and Varroa populations used in this study (Strauss et al 2013). This is in contrast to other parts of the world where Varroa mites and honeybee viruses are very prevalent and may have contributed to the weakening and mortality of a significant number of honeybee colonies (Berthoud et al 2010;Genersch et al 2010;Martin et al 2012;Francis et al 2013). …”
Section: Discussionmentioning
confidence: 84%
“…V. destructor mites have caused both an increase in viral load and prevalence of several RNA viruses in western honeybee populations , including DWV (Martin et al . 2012), ABPV (Genersch & Aubert 2010) and SBPV (Carreck, Ball & Martin 2010; Santillán‐Galicia et al . 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of DWV, the arrival of V. destructor has been directly linked to increased prevalence and virus loads in honeybees (Martin et al . 2012). …”
Section: Introductionmentioning
confidence: 99%